Vilniaus lietuvių periodiniai leidiniai (1904–1940) - Griškevičienė, Mirga Marija; Petrauskienė, Zofija Milda (Knygotyra, 1993)
One of the most complicated periods in the history of Lithuanian print is the publishing of periodicals in 1904–1940 by Vilnius Lithuanians. The daily „Vilniaus žinios“ (News of Vilnius) was the first Lithuanian newspaper to be published in Vilnius in 1904 after abolishing the prohibition of Latin alphabet in print in Lithuania. Vilnius became the main centre of Lithuanian print and the number of titles of periodicals increased. But the government changes during and after World War I and the occupation of Vilnius territory by Polish legionaries in 1920 had a negative influence upon the publishing work and prevented cultural development among Vilnius Lithuanians for several decades even.In 1904–1940 Lithuanians in Vilnius had published 283 periodicals and for the informational purposes part of them were in Polish and Russian languages. The permission for publishing used to be given only to persons of 21 year old and to those who havn’t been convicted and were the citizens of the country. Very often various persons were to sign and take the responsibility upon themselves for the publishing any newspaper or magazine. Now there are known 18 publishers and 189 editors; 25 publications are anonymous. We were lucky to ascertain 34 real publishers and editors and such outstanding Lithuanian public men as M. Biržiška. P. Karazija, K. Čibiras, V. Budrevičius, A. Burokas and others were among them. Complete sets of Lithuanian periodicals may be find in Vilnius Scientific Libraries.